Hubungan antara Kelekatan Pemuda-Orang Tua dan Dukungan Iman Orang Tua dengan Religiositas Intrinsik pada Pemuda Gereja-Gereja Injili di Bandung - Setiawati, Linda Christine; Mamahit, Aileen P.; Soeherman, Sylvia (Sekolah Tinggi Teologi SAAT, 2019)
The Relationship Between Parental Attachment and Faith Support with Intrinsic Religiosity of Emerging Adults from Evangelical Churches in Bandung. This study aims to find answers to research questions, namely whether or not there is a relationship between parental attachment and faith support with intrinsic religiosity of emerging adults from evangelical churches in Bandung. The research method used is quantitative by distributing questionnaires to 226 youth aged 18-29 years and not married in 8 evangelical churches in Bandung. The results showed a significant relationship between youth-mother attachment with intrinsic religiosity of youth. Youth-father attachment was not found to be related to intrinsic religiosity, nor was parental support of faith.